PENGARUH ADAPTABILITAS PEMASARAN TERHADAP KINERJA PEMASARAN MELALUI HUBUNGAN DENGAN PELANGGAN DAN KEUNGGULAN BERSAING - Suliyanto, Suliyanto (Performance, 2011)
Puposes of this study were to explain the influence of marketing adaptabilitation on customer relationship and competitive advantage olso to analysis influence of customer relationship and competitive advantage on marketing performance. To test the empirical models, Structural Equation Modeling (SEM) was used. Sample size of this research were 200 owners and/or managers of Small and Medium Enterprises (SMEs) running food and beverage sector in the residency Banyumas areas. The results showed that marketing adaptabilitation has a positive effect on customer relationship and competitive advantage, customer relationship and competitive advantage on marketing performance.